A population‐based epidemiological study of neuromyelitis optica spectrum disorder in Hungary. (30th September 2019) - Papp, V.; Iljicsov, A.; Rajda, C.; Magyari, M.; Koch‐Henriksen, N.; Petersen, T.; Jakab, G.; Deme, I.; Nagy, F.; Imre, P.; Lohner, Z.; Kovács, K.; et al.
Abstract : Background and purpose: The goal of this study was to determine the prevalence and incidence of neuromyelitis optica spectrum disorder (NMOSD) in Hungary based on the 2015 International Panel of NMO Diagnosis (IPND) criteria. Methods: A retrospective population‐based cohort study was conducted of 6.4 million Hungarians (age ≥ 16 years) between 1 January 2006 and 31 December 2016. Possible NMOSD patients were selected via multistage re‐evaluation from multiple sources. Crude and sex‐ and serostatus‐specific prevalence (per 100 000 persons) and incidence rates (per 1 000 000 person‐years) from 2006 to 2015 were estimated and age‐adjusted rates were determined. Results: Of 2262 study candidates, 154 NMOSD patients (age ≥ 16 years) with onset until 31 December 2016 were identified based on 2015 IPND criteria. The prevalence analysis on 1 January 2016 included 123 NMOSD living cases, resulting in a prevalence of 1.91 [95% confidence interval (CI) 1.52–2.28] per 100 000 persons. The 101 incident cases emerging from the observed 76 394 288 person‐years provided an incidence rate of 1.32 (95% CI 1.08–1.61) per 1 000 000 person‐years. Age‐adjusted prevalence was 1.87 (95% CI 1.56–2.23) per 100 000 persons and incidence was 1.20 (95% CI 0.98–1.46) per 1 000 000 person‐years. Conclusions: In this first report of a large population‐based epidemiological study from an Eastern European Caucasian population using robust case validation, a greater prevalence and incidence of NMOSD was found compared to previous large studies in Caucasian populations.